Interactive Multiple Criteria Decision Making based on preference driven Evolutionary Multiobjective Optimization with controllable accuracy - Kaliszewski, Ignacy; Miroforidis, Janusz; Podkopaev, Dmitry (European journal of operational research, 2012)
► Human preferences drive evolutionary computations for interactive MCDM processes. ► Decision making processes are based on lower and upper bounds on outcomes. ► Evolutionary computations explore regions of feasible and infeasible variants. ► Two evolutionary algorithms are proposed and a numerical example is solved. We present an approach to interactive Multiple Criteria Decision Making based on preference driven Evolutionary Multiobjective Optimization with controllable accuracy. The approach relies on formulae for lower and upper bounds on coordinates of the outcome of an arbitrary efficient variant corresponding to preference information expressed by the Decision Maker. In contrast to earlier works on that subject, here lower and upper bounds can be calculated and their accuracy controlled entirely within evolutionary computation framework. This is made possible by exploration of not only the region of feasible variants – a standard within evolutionary optimization, but also the region of infeasible variants, the latter to our best knowledge being a novel approach within Evolutionary Multiobjective Optimization. To illustrate how this concept can be applied to interactive Multiple Criteria Decision Making, two algorithms employing evolutionary computations are proposed and their usefulness demonstrated by a numerical example.